Case Report: Balancing immunosuppression and infection—intravenous immunoglobulin in anti-HMGCR immune-mediated necrotizing myopathy complicated by severe pneumonia - Jing Fu; Qiong Zhao; Jing-Bo Lou; Gui-Hua Tang; Wei Chen; Jiang-Hu Zhao; Qian-Song He (Frontiers in Medicine, 2026)
A 65-year-old male with a 3-year history of atorvastatin use presented with progressive proximal muscle weakness, dysphagia, and markedly elevated creatine kinase (2,277 U/L). Initially misdiagnosed with polymyositis, he deteriorated with severe pneumonia, septicemia, and type I respiratory failure requiring mechanical ventilation. Interleukin-6 rose from 12.83 to 610.9 pg/mL during sepsis. After confirmation of anti-HMGCR antibody positivity (18 arbitrary units [AU], cutoff >10 AU) via line blot assay, we discontinued methotrexate, maintained methylprednisolone at 40 mg, and initiated intravenous immunoglobulin (IVIG) 0.4 g/kg/day for 5 days with broad-spectrum antibiotics. Within two weeks, proximal muscle strength (MRC scale) improved from 2/5 to 4/5, IL-6 normalized to 8.56 pg/mL, and respiratory failure resolved. This case suggests that IVIG may serve as a safe immunomodulatory bridge in critically ill IMNM patients with severe infections.